Peran Ibu Terhadap Kesiapan Anak Bersekolah - Santi Handayani; Rena Latifa (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
Children’s school readiness includes ready school, ready family and ready children themselves. This research aims to observe whether a mother’s support, mother-child attachment and demographic factor could affect an elementary grader’s school readiness. The subjects in this research are 202 students’ mothers. This research used purposive sampling and quantitative method. The validity of the instrument was tested by Confirmatory Factor Analysis (CFA). Meanwhile, the data was analyzed by using multiple regression analysis. The results of this research were shown that mother’s support and gender together influence school readiness. Whereas the variable of mother-child’s attachment, school entry age, working mother status, child’s birth order were not statistically proven to be influential on school readiness.